Increased perceived autonomy-supportive teaching in physical education classes changes students’ positive emotional perception compared to controlling teaching - Leisterer, Sascha; Paschold, Elias (Frontiers in Psychology, 2022)
Teachers can expect that autonomy support positively influences students’ affective-emotional perception in physical education (PE), when considering assumptions of the Self-Determination theory. Highly autonomy-supportive PE teaching comprises students’ free choices regarding organizational, procedural, and cognitive aspects of a PE lesson, whereas low autonomy support addresses these aspects only partly and controlling teaching refers to students as recipients of the teacher’s decisions. This quasi-experiment investigates effects to determine the effects of high autonomy-supportive (PEhigh), low autonomy-supportive (PElow) and controlling (PEcontrol) PE class teaching styles on affective valence and enjoyment. As such, we compare the effects of these teaching styles on beneficial psychological outcomes (i.e., affective valence, enjoyment) in students. In a sample of German students (N = 57; age: M ± SD = 15.6 ± 0.6; gender: 53% female, 47% male) perceived autonomy support, affective valence, and enjoyment were assessed via self-report questionnaires before and after a 20-min PE class intervention focusing on high or low autonomy-supportive, or controlling teaching. Students who participated in PEhigh perceived significantly more positive valence and enjoyment over time compared to students in the PElow and PEcontrol groups (affective valence: p = 0.025, ηp2 = 0.13; enjoyment: p = 0.007, ηp2 = 0.17). Differences between groups show significant results for valence between PEhigh and PEcontrol, and between PElow and PEcontrol. Thus, PEhigh should be preferred over PElow to intensify these effects. Based on these results, PE teachers can employ a high autonomy-supportive teaching style (e.g., through a combination of free choices, social interaction, and informative feedback) to improve students’ positive affective-emotional perception and to foster an increase in students’ time engaged in physical activity.